Species-Specificity in Thermopreference and CO2-Gated Heat-Seeking in Culex Mosquitoes - Joanna M. Reinhold; Karthikeyan Chandrasegaran; Helen Oker; José E. Crespo; Clément Vinauger; Chloé Lahondère (Insects, 2022)
Combining thermopreference (Tp) and CO2-gated heat-seeking assays, we studied the thermal preferendum and response to thermal cues in three Culex mosquito species exhibiting differences in native habitat and host preference (e.g., biting cold and/or warm-blooded animals). Results show that these species differ in both Tp and heat-seeking behavior. In particular, we found that Culex territans, which feed primarily on cold-blood hosts, did not respond to heat during heat-seeking assays, regardless of the CO2 concentration, but exhibited an intermediate Tp during resting. In contrast, Cx. quinquefasciatus, which feeds on warm blooded hosts, sought the coolest locations on a thermal gradient and responded only moderately to thermal stimuli when paired with CO2 at higher concentrations. The third species, Cx. tarsalis, which has been shown to feed on a wide range of hosts, responded to heat when paired with high CO2 levels and exhibited a high Tp. This study provides the first insights into the role of heat and CO2 in the host seeking behavior of three disease vectors in the Culex genus and highlights differences in preferred resting temperatures.